Porf-2 Inhibits Neural Stem Cell Proliferation Through Wnt/β-Catenin Pathway by Its GAP Domain - Huang, Guo-Hui; Yang, Xi-Tao; Chen, Kui; Xing, Jin; Guo, Lin; Zhu, Liang; Li, Hong-Jiang; Li, Xin-Cai; Zhang, Sheng-Yi; Feng, Dong-Fu (Frontiers in Cellular Neuroscience, 2016)
Neural stem cell (NSC) proliferation and differentiation play a pivotal role in the development of brain, the plasticity of the brain network and the repair for brain function in CNS diseases. The mechanisms regulating NSC behavior are not well elucidated. Previous studies showed porf-2 functions as a modulator in central nerve system development. We here show that porf-2, a conserved family of RhoGAPs, is highly and specifically expressed in NSCs. We also demonstrate that porf-2 inhibits the proliferation of NSCs in vivo and in vitro, but has no effect on NSC differentiation. We investigated which domain is required for the role of porf-2 on NSC proliferation. By using neurosphere formation and Edu assay we confirmed the GAP domain is necessary for its function. In addition, we surveyed a few classical pathway on NSC proliferation and found that porf-2 inhibits NSC proliferation by suppressing the β-catenin nuclear translocation. Taken together, we show for the first time that porf-2 inhibits NSC proliferation through Wnt/β-catenin pathway by its GAP domain.